Basic Security Challenges in Cloud Computing - Rizwan, Syed; Zubair, Muhammad (2019 4th International Conference on Emerging Trends in Engineering, Sciences and Technology (ICEEST), 2019)
With the advancement in information technology, everyone moves towards pleasure, ease, and luxury. From which the most advanced and usable field is Cloud Computing which uses the internet and gives access to storing the data to the user. It has many characteristics like elasticity, extensibility, smartness and lower cost, which causes companies to address the clients' requirements. In spite of this, associations are delayed in accommodating it because of security issues and difficulties related with it. The development of cloud is affected by the security. This paper gives ongoing advances in cloud computing and highlights on some challenges, security issues, and solutions. It also incorporates the basics of cloud computing to make itself contained so that pursuers can have a reasonable comprehension of the subject and cloud computing security.